Photo degradation of Lanthanum (III) Complex with 1, 2 , 4-Thiadiazole in Dimethyl Sulsoxide ( DMSO ) Solvent (Journal of the College of Basic Education, 2022)
5- Amino -3- [4- O- hydroxypheny Ithiosemi carbazido ] -1,2,4-thiadiazole compound has been prepared by the reaction of ( 3-mercapto -5- ami,2,4- thiadiazole) with ( O-hydroxyphenyl thiosemicarbazide) in mole ratios of (1:1) .The ligand has been characterized and its structure was elucidated depending upon the spectral data of IR and U.V-Vis spectra . Lanthanum complex of the formula [La( C9H10N6S2O)2Cl2]Cl was prepared through the reaction of the prepared ligand with lanthanum chloride in mole ratios (2:1) respectively . The mode of bonding and overall geometry of the complex was determined through physicochemical and spectroscopic methods . The kinetic of the photo-degradation of the prepared complex was investigated and it was the first order and the rate constant (Kd) determined at (25oC ) Further more primary quantum yields (Φ) has been also calculated.